Identification of Phyllanthus niruri by FTIR spectroscopy with chemometrics - Kartini Kartini; Devi Hardianti; Mochammad Arbi Hadiyat (Universitas Ahmad Dahlan, 2021)
Phyllanthus niruri (Indonesian: meniran) is a crude drug used in scientific jamu for hyperuricemia, mild hypertension, osteoarthritis, hemorrhoids, and hypercholesterolemia. This plant contains various bioactive compounds such as flavonoids, terpenes, coumarins, lignans, tannins, saponins, alkaloids, etc. Phyllanthus niruri is a wild plant growing in the tropics and sub-tropics of Asia, America, and China. This herb grows well from the lowlands to the highlands, such as bushes, terrain, yards, roadsides, gardens, and rivers. The levels of active compounds in a plant can vary depending on many factors, such as growing location, temperature, humidity, rainfall, and others. This research aimed to evaluate and differentiate P. niruri herbs according to their geographical location using FTIR fingerprint coupled with chemometrics, Principal Component Analysis (PCA) and Cluster Analysis (CA). The results of this study showed that 14 samples of P. niruri are classified into two groups. The first group consists of P. niruri powder originating from Tawangmangu, Kediri, Surabaya, Bangkalan, Gresik, Mojokerto, Kertosono, Krian, Blitar, Nganjuk, unknown 1, unknown 2, and unknown 3, whereas the second group consists of only one sample from Pasuruan. In conclusion, FTIR fingerprint analyzed with chemometrics is adequate to differentiate the powder of P. niruri collected from different locations. FTIR fingerprints combined with chemometrics can be further considered as a method in the quality control process of P. niruri.